2016
DOI: 10.1074/jbc.m116.727875
|View full text |Cite
|
Sign up to set email alerts
|

The MET/Vascular Endothelial Growth Factor Receptor (VEGFR)-targeted Tyrosine Kinase Inhibitor Also Attenuates FMS-dependent Osteoclast Differentiation and Bone Destruction Induced by Prostate Cancer

Abstract: The tyrosine kinase inhibitor TAS-115 that blocks VEGF receptor and hepatocyte growth factor receptor MET signaling exhibits antitumor properties in xenografts of human gastric carcinoma. In this study, we have evaluated the efficacy of TAS-115 in preventing prostate cancer metastasis to the bone and bone destruction using the PC3 cell line. When PC3 cells were injected into proximal tibiae in nude mouse, severe trabecular and cortical bone destruction and subsequent tumor growths were detected. Oral administr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…5,7,[14][15][16] This axis is also important in oncogenesis and plays a significant role in the migration, proliferation and adhesion of various neoplastic cells. Overexpression or excessive activation of HGF/MET has been demonstrated in mesenchymal and epithelial tumors such as breast cancer, ovarian cancer, gastrointestinal tract cancer, lung cancer, prostate cancer, glioblastoma, sarcomas, and MM.…”
Section: Discussionmentioning
confidence: 99%
“…5,7,[14][15][16] This axis is also important in oncogenesis and plays a significant role in the migration, proliferation and adhesion of various neoplastic cells. Overexpression or excessive activation of HGF/MET has been demonstrated in mesenchymal and epithelial tumors such as breast cancer, ovarian cancer, gastrointestinal tract cancer, lung cancer, prostate cancer, glioblastoma, sarcomas, and MM.…”
Section: Discussionmentioning
confidence: 99%
“…Additional proof for the direct effect of cabozantinib in prostate cancer tumour cells, endothelial cells and osteoblasts was provided by patient derived xenografts and clinical trials [175]. A study with TAS-115, another MET/VEGFR inhibitor that also inhibits FMS, demonstrated an osteolysis prevention effect (PC-3 model) due to prostate cancer cell and osteoclast targeting (the latter via inhibition of FMS-dependent RANKL-induced pre-osteoclast to osteoclast differentiation) [176]. Similar results emerged from a model of bone metastatic lung carcinoma [177].…”
Section: Emerging Bone Targeting Therapiesmentioning
confidence: 99%
“…The role of BSI in the management of patients with prostate cancer will be analyzed after a follow‐up period of 3 years. A new phase 2 clinical study is under investigation in patients with CRPC (JapicCTI‐163448) in Japan to assess the efficacy and safety of TAS‐115 (vascular endothelial growth factor receptor‐targeted tyrosine kinase inhibitor; Taiho Pharmaceutical, Tokyo, Japan) . The primary outcome of that study uses BSI calculated with BONENAVI software.…”
Section: Perspectives In Japanmentioning
confidence: 99%
“…A new phase 2 clinical study is under investigation in patients with CRPC (JapicCTI-163448) in Japan to assess the efficacy and safety of TAS-115 (vascular endothelial growth factor receptor-targeted tyrosine kinase inhibitor; Taiho Pharmaceutical, Tokyo, Japan). 22 The primary outcome of that study uses BSI calculated with BONE-NAVI software. BSI could be a good surrogate marker for evaluating the effects of potentially useful new drugs for bone metastasis.…”
Section: Perspectives In Japanmentioning
confidence: 99%